2011
DOI: 10.1177/1748048511420094
|View full text |Cite
|
Sign up to set email alerts
|

News use and political socialization among young Jordanians

Abstract: This study examined the relationship between young Jordanians' ( N = 321) news use and their feelings toward the Jordanian and US governments. Consumption of traditional news delivery formats (such as print newspapers, radio broadcasts and interpersonal sources) was measured, as was reliance on new media formats such as blogs, text messaging and podcasting. Political socialization measures were indices of political trust and appraisals of the US government. Results suggest that young Jordanians in the sample r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…News use has not always been found to predict favorable ratings of countries, though. Martin (2011) found that TV news use was associated with negative views of the U.S. among young Jordanian adults. Risso (2018) discussed the role of Cambridge Analytica targeting certain consumers with “Leave”-supportive Brexit news, which fanned negative attitudes in the UK toward the E.U.…”
Section: The Halo Effectmentioning
confidence: 96%
“…News use has not always been found to predict favorable ratings of countries, though. Martin (2011) found that TV news use was associated with negative views of the U.S. among young Jordanian adults. Risso (2018) discussed the role of Cambridge Analytica targeting certain consumers with “Leave”-supportive Brexit news, which fanned negative attitudes in the UK toward the E.U.…”
Section: The Halo Effectmentioning
confidence: 96%